AN ANALYSIS OF NIHILISM IN MODERN SOCIETY: A STUDY OF AMERICAN PSYCHO AND EVERYTHING EVERYWHERE ALL AT ONCE - Somanath, Sandra; Devi K (International Journal of Research -GRANTHAALAYAH, 2025)
Through thoroughly examining two culturally significant films, American Psycho (2000) and Everything Everywhere All at Once (2022), this research paper explores the ubiquitous theme of nihilism in contemporary society. This analysis will look at how each movie both reflects and challenges nihilistic ideologies, providing opposing viewpoints on the pursuit of meaning in a world that is becoming more and more disjointed and disillusioned. By contrasting these two movies, the study seeks to reveal how nihilism is portrayed in various genres and eras and how it reflects societal concerns about morality, identity, and purpose. Although philosophy and classic literature have written a great deal about nihilism, little attention has been paid to how nihilistic themes are portrayed in modern films like American Psycho and Everything Everywhere All at Once about contemporary societal issues, especially identity crises. Few studies have looked at the relationship between nihilism and the pursuit of self-identity and personal meaning, particularly in a consumer-driven society like that portrayed in American Psycho, or the more general existential issues discussed in Everything Everywhere All at Once. This disparity emphasises the need for a more thorough examination of how contemporary film reflects and critiques nihilistic ideologies via the prism of psychological and cultural issues.